2023
DOI: 10.1111/jopy.12812
|View full text |Cite
|
Sign up to set email alerts
|

How and why people want to be more moral

Abstract: What types of moral improvements do people wish to make? Do they hope to become more good, or less bad? Do they wish to be more caring? More honest? More loyal? And why exactly do they want to become more moral? Presumably, most people want to improve their morality because this would benefit others, but is this in fact their primary motivation? Here, we begin to investigate these questions. Across two large, preregistered studies (N = 1,818), participants provided open-ended descriptions of one change they co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This conclusion aligns well with recent findings on the question of why people want to become more moral. Sun et al (2023) found that the extent to which people believe that changes would benefit their well-being was the best predictor of their motivation to increase moral traits. Our findings support their interpretation that the belief that one will become happier as a result of changing one's personality traits is an important mechanism to be considered in studying volitional personality change.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion aligns well with recent findings on the question of why people want to become more moral. Sun et al (2023) found that the extent to which people believe that changes would benefit their well-being was the best predictor of their motivation to increase moral traits. Our findings support their interpretation that the belief that one will become happier as a result of changing one's personality traits is an important mechanism to be considered in studying volitional personality change.…”
Section: Discussionmentioning
confidence: 99%
“…Following comprehensive investigations of the structure of personality based on lexical studies of thousands of personality trait descriptors (Allport & Odbert, 1936; John et al., 2008; Saucier & Goldberg, 1996), personality psychology also offers established trait taxonomies that can be used as organizing frameworks (Bainbridge et al., 2022; Irwing et al., 2023). For example, Sun and colleagues (2024) use dimensions from the Big Five facets, VIA character strengths, and MFT to categorize people's moral improvement goals. Illustrating the limitations of the dominant MFT framework, goals reflected all 20 categories (as well as an “Other” category), including 15 categories that are not represented in MFT (e.g., honesty, bravery, productiveness).…”
Section: Contributions Of Personality Psychologymentioning
confidence: 99%
“…Fleeson and colleagues (2024) and Helzer and colleagues (2024) use nomination procedures that enable the study of those who are perceived as being moral exemplars in general, or within an MBA classroom. Sun and colleagues (2024) use open‐ended responses to comprehensively describe people's ordinary concepts of moral improvement. Baumert and colleagues (2024) use the experience sampling method to capture real‐world instances of moral courage when people are confronted with others' norm violations.…”
Section: Contributions Of Personality Psychologymentioning
confidence: 99%
See 1 more Smart Citation